Linguo-cognitive model of word polysemy with the semantics of human cognitive activity - Чернцова, Елена (Slavia Centralis, 2021)
For the first time, a linguistic cognitive model has been proposed to explain the emergence of new meanings of a word; conclusions have been put forward about the role of each discourse and "its rules" in the "development" of a system of discursive meanings of a word. The theoretical idea that linguistic semantics is driven by the subject’s discursive activity as well as its cognitive experience and knowledge was verified. The integral, cognitive and discourse method allowed us to represent the system of discourse-related meanings of words (concepts), summarise a "sum" of the meanings of the words received, as well as identify the repeated structure of cognitive processes which reflect the templates of thinking and understanding. In addition, it enabled us to reconstruct a gestalt scenario and offer metacognitive representation of the conceptual field researched.